Optimasi Komposisi Ekstrak Etanol Herba Ciplukan dan Kulit Buah Pinang menggunakan Metode Simplex Lattice Design dengan Parameter Daya Hambat Bakteri - Ismaurasi, Marcelina Fransisca Alecia; Rollando; Yanuar, Michael Resta Surya (Program Studi Farmasi, Universitas Ma Chung, 2024)
Indonesia has a diversity medicinal plants as traditional medicine. Traditional medicine has shortcomings in the use of the main composition and components used, making it less effective. Therefore, medicinal plants need to be optimized in composition and add two or more plants to maximize treatment. Medicinal plants can be antibacterial. Indonesia has the ciplukan and areca nut plants that have antibacterial potential. There are 5 stages of work procedures in the research method. The first is plant determination. The second is the optimization composition using the simplex lattice design method. The third is extraction by the maceration method. The fourth is an antibacterial activity test. The last of data analysis uses software design experts and SPSS. The results were composition optimization with the simplex lattice design method resulting in 8 compositions. The results of the antibacterial activity test were presence of antibacterial activity in composition 7 (87.5 μg and areca nut shell 62.5 μg) with an inhibition diameter of 11.32 mm and composition number 8 (62.5 μg and areca nut shell 87.5 μg) with an inhibition diameter of 11.58 mm. The final result of the confirmation of composition 8 has the strongest antibacterial potential shown by the diameter of inhibition of 15.27 mm and the desirability value, which is 1.